A general guide to design of falling film evaporators utilized in multi effect desalination units operating at high vapor qualities under a sub-atmospheric condition. (1st May 2015) - Bigham, S.; KouhiKamali, R.; P. Zadeh, M.
Abstract: Existing heat transfer correlations poorly predict the thermal performance of falling film evaporators utilized in MED (multi effect desalination) units. At typical operating conditions of these units, most correlations suggest that the two-phase heat transfer coefficient increases with the mass flow rate and is independent of the wall superheat. Although these correlations are valid within their particular range of parameters, they are not suitable prediction tools for MED units as they operate at high vapor qualities under a sub-atmospheric condition. In addition, strong interconnected effects of the wall superheat and the mass flow rate on the thermal performance are often unavoidable in the MED units. The present study aims to elucidate the thermal transport processes of the falling film evaporators utilized in these MED units. Results show, at a constant value of Δ T / m ˙ f which is a design characteristic of these units, the average heat transfer coefficient first decreases and then increases as the inlet mass flow rate increases. Result also indicate the wall superheat for this transition increases at higher values of Δ T / m ˙ f . The detailed thermo-hydrodynamic physics of the involved transport processes is elucidated using the VOF (volume of fluid) multiphase model in the curvilinear coordinate. Highlights: Falling film evaporators utilized in sub-atmospheric, high vapor quality MED (multi effect desalination) units are analyzed. The interconnected effects of the wall superheat and the inlet mass flow rate are elucidated. The thermal performance curves of the MED units are extracted and analyzed.